Intraepidermal Epidermotropic Metastatic Melanoma: a Clinical and Histopathological Mimicker of Melanoma in Situ Occurring in Multiplicity - Lestre, S (2012)
The distinction between primary melanoma and melanoma metastatic to the skin has major prognostic implications. We report a case of a 67-year-old male with a diagnosis of a superficial spreading melanoma (stage IB) rendered 6 years earlier who presented clinically with an atypical nevus on his left thigh. Histopathological examination showed an intraepidermal melanocytic proliferation that was interpreted as melanoma in situ. Subsequently, 45 additional pigmented macules appeared in crops over a 9-month period. Clinically and dermoscopically, these lesions were extremely polymorphic. Histopathological findings were compatible with melanoma in situ, as each lesion consisted of a wholly intraepidermal proliferation of markedly atypical melanocytes arranged singly and in nests. A complete gastrointestinal study showed multiple pigmented metastatic lesions throughout the stomach and small bowel, which supported a diagnosis of metastatic melanoma with gastrointestinal and epidermotropic skin involvement. Monosomy of chromosome 9 and a BRAF V600E mutation were detected in the primary tumor sample and in macro-dissected secondary lesions. No CDKN2A or CDK4 germline mutations were found. Intraepidermal epidermotropic metastases of melanoma have been rarely described in literature. In this case, histopathology alone was insufficient to distinguish metastatic melanoma from multiple in situ melanomas. The recognition of epidermotropic metastases should be based on the correlation between clinical, dermoscopic, histopathological and molecular findings.